Improving development aid design and evaluation: Plan for sailboats, n ot trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from tradition al technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fu nd or implement such programmes evaluate whether their efforts are con tributing to reform? This report …
Keywords: IMPORTANT